A HORNBILL PATTERN DESIGN FOR OUTER KIMONO - Purwanto, Muhammad Rifky (Arty: Jurnal Seni Rupa, 2022)
This design processes the visual form of the hornbill to be used as a motif design that is applied to a ready-to-wear outer kimono with a Kalimantan ethnic theme. The formulation of the problem in this design is to convey an issue that occurs in the hornbill with textile fashion media that will be used by teenagers-adults with an age range of 20-30 years. This design uses a design approach that goes through several processes, namely; exploration, extraction, termination point (Palgunadi, 2007:266-268). Through this approach, the author explores and explores information related to the concept as a whole, and analyzes the design made to determine the conclusions and solutions made in order to determine the existing conclusions and solutions. The result of this design is an outer kimono that has a hornbill motif design with a typical appearance of the Kalimantan ethnic. Processing the motif design into cloth will use the concept of batik technique with a mixture of hot paraffin wax as a color barrier medium, and the visualization of the work is made as relative as possible with the typical pattern of the Dayak Kalimantan tribe.